International Adoption: The Whys and Hows - Brianne McCarthy; Carolyn Wilken (EDIS, 2005)
Many people in the United States choose to adopt children into their families. Over the last ten years, it has become very popular to internationally adopt. Although the international adoption process is complex, it is very rewarding for the new family. This document is FCS2234, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published June 2005.